Pengaruh Metode Pictorial Riddle terhadap Penguasaan Konsep Fisika SMP - Terry Arlana; Siti Anisatur Rofiqah; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2020)
The purpose of this study was to determine the effect of the application of the pictorial riddle learning method on the mastery of physics concepts for class VIII students of SMP Negeri 2 Buay Madang in the 2020/2021 academic year. This research was an experimental research with a quasi-experimental design. The population in this study were all students of class VIII SMP Negeri 2 Buay Madang, totaling 49 students. The samples of this research were students in class VIII A, which amounted to 25 students as the experimental class, and class VIII B, which consisted of 24 students as the control class. The data collection method in this research was the test method. The data analysis used was a statistical test using the t polled variant t test statistical formula. Based on data analysis using the t polled variant test, it was concluded that the results of the posttest physics of students learning with the pictorial riddle method were high. Of the 25 students, there were 15 students (60%) who scored in the high category, and the average score of the class posttest results was 78.58. The results of the posttest physics of students who learned using conventional methods were in the low category, from a total of 24 students, 12 students (50%) obtained low category scores, and the average score of posttest results was 67.75. Therefore, it can be concluded that there is an effect of the application of the pictorial riddle method on mastery of physics concepts in class VIII of SMP Negeri 2 Buay Madang for the 2020/2021 academic year with a tcount of 7.37 while ttable is 1.98. Because tcount score is not located between - ttable ≤ tcount <+ ttable, which is -1.98 and +1.98, so H0 is rejected and H1 is accepted.